Probing Dust and Grain Growth in the Optically Thick Circumbinary Ring of v892 Tau - Miley, J (EDP Sciences, 2025)
Context. A considerable proportion of young stars belong to multiple star systems. Constraining the planet formation processes in multiple stellar systems is then key to understanding the global exoplanet population. Aims. This study focuses on investigating the dust reservoir within the triple system V892 Tau. Our objective is to establish constraints on the properties and characteristics of the dust present in the system s circumbinary ring. Methods. Based on archival ALMA and VLA data from 0.9 mm to 9.8 mm, we present a multi-wavelength analysis of the ring of V892 Tau. We first studied the spatial variation of the spectral index, before employing 3D full-radiative-transfer calculations to constrain the ring s geometry and the radial dependence of the dust-grain properties. Results. Spectral indices are consistent with non-dust emission in the vicinity of the central binary, and with dust emission in the ring likely remaining optically thick up to 3.0 mm. Our radiative transfer analysis supports these interpretations, yielding a model that reproduces the observed intensities within the 1σ uncertainties across all wavelengths. The resulting dust-surface density and temperature profiles both decrease with increasing radius, and are in agreement with values reported in the literature. Maximum grain sizes are constrained to 0.2 cm, with a size distribution power-law index -3.5. These results imply that the dust-grain fragmentation velocity does not exceed 8 m s-1. Conclusions. Whilst our results suggest dust trapping at the cavity edge, they also suggest that tidal perturbations triggered by the central binary limit grain growth within the ring. This highlights the need to further constrain planet formation efficiency in multiple stellar systems, a goal that may be advanced by applying the methodology of this work to a wider sample of systems. © The Authors 2025.